Penerapan Metode Self Delimiting Codes Dalam Kompresi File - Chyintia Berliana Simbolon (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Data compression is a technique to reduce the amount of data size (compression results) from the original data. Data compression is generally applied to computer machines, this is done because each symbol that appears on the computer has a different bit value. The analysis is carried out in the process of working of the Self Delimiting Codes Algorithm. This compression technique is to build self-delimiting code, codes that have variable length and can be clearly translated to produce an algorithm output in the form of a binary string or code that translates each input string so that the string has a small number of bits compared to an uncompressed string.